ANALISIS ISI KEKERASAN FISIK DAN PSIKOLOGIS DALAM FILM PARASITE KARYA BONG JOON-HO - Morrison Joshua, Glenkevin; Pradipta, Ade Devia; Alit Suryawati, I Gusti Agung (E-Jurnal Medium, 2020)
ABSTRACT Bong Joon-ho's Parasite film is one of the most critically acclaimed films in 2019 with its genre of dark humor, thriller, and drama. These genres known to be dealing with violent scenes. Researcher wanted to know what are the physical and psychological violence scenes in Parasite film in a descriptive quantitative manner. Researcher is assisted by two coders to record every physical and psychological violence scenes based on indicators of violence from Harsono Suwardi. Result shows that Parasite film displays 107 physical and psychological violence scenes. Psychological violence is the dominating one with a total of 69 times, with its dominating scenes to be yelling and degrading, 18 times. While physical violence appears with a total of 38 times, with its dominating scene to be injuring with bare hands or with tools, 16 times. Thus, female do the most violence in Parasite film.   Keywords: Content Analysis, Film, Physical Violence, Psychological Violence